2011
DOI: 10.1177/0022146510395025
|View full text |Cite
|
Sign up to set email alerts
|

The Third Therapeutic System

Abstract: Faith healing in sub-Saharan Africa has primarily been studied qualitatively among Pentecostal-Charismatic groups, and considered as its own phenomenon with little attention to its relationship to other modes of healing. Using data from Malawi, a religiously diverse African country with high HIV prevalence, we find that faith healing is pervasive across multiple religious traditions. For individuals, attending a faith healing congregation is associated with lower levels of generalized worry about AIDS, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…We further validate the measure by comparing the predictive power of likelihood of current infection (measured with beans) to another commonly used subjective measure—worry about HIV (see Manglos and Trinitapoli 2011; Smith and Watkins 2005). Figure 3 demonstrates the superior predictive power of the beans method for actual HIV status.…”
Section: Resultsmentioning
confidence: 99%
“…We further validate the measure by comparing the predictive power of likelihood of current infection (measured with beans) to another commonly used subjective measure—worry about HIV (see Manglos and Trinitapoli 2011; Smith and Watkins 2005). Figure 3 demonstrates the superior predictive power of the beans method for actual HIV status.…”
Section: Resultsmentioning
confidence: 99%
“…Second, they tend to involve situations that are prime opportunities for perceived miraculous intervention, such as uncertain medical prognoses or unexpected recoveries. Studies have indeed suggested that experiences of healing are powerful motivators of religious commitment, and that at the societal level, religious movements that emphasize spiritual experience and an individual bond with God often interpret sickness and trauma in religious terms (Dilger 2007; Manglos and Trinitapoli 2001; Poloma and Hoelter 1998). …”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, research has found returning to HIV care to be associated with spirituality among U.S. inner-city clinic patients [51]; concurrent use of complementary and alternative medicine to be associated with less adherence to HIV medications in China [52]; and, faith healing to be “the third therapeutic system” in HIV management in sub-Saharan Africa [53]. …”
Section: Introductionmentioning
confidence: 99%